2016
DOI: 10.1016/j.jvs.2016.06.098
|View full text |Cite
|
Sign up to set email alerts
|

Possible consequences of regionally based bundled payments for diabetic amputations for safety net hospitals in Texas

Abstract: Regions with a high proportion of safety net hospitals perform almost half of the diabetic amputations in Texas. Changes to traditional payment models should account for the disproportionate burden of high-risk procedures performed by these hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Trends such as these are important to identify as adult reconstruction surgery moves toward bundled payment programs, particularly while considering that lower socioecomic status is associated with an increased risk of undergoing GRA. For example, in a study of diabetes-related amputations, Newhall et al 27 found that these procedures were over 50% more common at safety net hospitals. Based on our findings, similar trends might be suspected regarding GRA.…”
Section: Discussionmentioning
confidence: 99%
“…Trends such as these are important to identify as adult reconstruction surgery moves toward bundled payment programs, particularly while considering that lower socioecomic status is associated with an increased risk of undergoing GRA. For example, in a study of diabetes-related amputations, Newhall et al 27 found that these procedures were over 50% more common at safety net hospitals. Based on our findings, similar trends might be suspected regarding GRA.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes included other diabetes-related conditions and procedures (tissue and bone debridement, peripheral vascular disease, and diabetic foot ulcer) commonly considered to be direct precursors or alternatives to LEA. Codes for all outcome definitions were informed through prior literature [20][21][22][23][24][25][26][27][28][29][30] and clinical guidance (Table S2). For secondary analyses, we excluded patients with baseline history of any outcome.…”
Section: Outcome Definitionsmentioning
confidence: 99%
“…To increase outcome specificity, we required FG diagnoses to either occur in an inpatient setting or be followed by a hospitalization within 7 days, and be additionally accompanied by systemic antibiotic, debridement, or related surgical procedure4 within 7 days (primary outcome definition). Codes were informed through prior literature15–25 and clinical guidance.…”
Section: Methodsmentioning
confidence: 99%